Legal Advocacy for Balanced Protection of Jastip Business Actors - Dian Afrilia; Joni Emirzon; Putu Samawati; Faiq Faiq (Indonesian Journal of Advocacy and Legal Services, 2026)
This study examines the legal protection of online personal shopping service (jastip) business actors within Indonesia’s rapidly evolving digital economy, where existing regulations remain largely consumer-oriented and do not adequately address the vulnerabilities faced by business actors. The research aims to analyze the legal structure of jastip agreements and evaluate whether current legal frameworks provide balanced protection for all parties involved. Using a normative juridical method with statutory and conceptual approaches, the study finds that jastip agreements have a hybrid contractual nature, combining elements of mandate, sale, deposit, and service contracts. Nonetheless, such agreements existing beyond the boundaries of civil law categories make legal uncertainty and unduly burdensome business actors, especially in relation to bad faith on behalf of consumers and wrongdoing by third-parties. This research is in line with the discourse by suggesting that law needs to set more proportionally business actors as subjects of protection, these regulations are yet to adequately accommodate and address digital intermediary practices, and therefore urges the need for specific creating adaptive regulation while optimizing electronic contracts as preventive regulatory instruments to secure fairness, legal certainty, and balance risks in jastip transaction.